Injikovatelný hydrogel funkcionalizovaný suspenzí bohatou na trombocyty a mikročásticemi pro urychlení regenerace chrupavky - Rampichová, M; Buzgo, M; Křížková, B; Prosecká, E; Pouzar, M; Štrajtová, L (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2013)
PURPOSE OF THE STUDY: Articular cartilage defects arise due to injury or osteochondral disease such as osteonecrosis or osteochondritis dissecans. In adult patients cartilage has minimal ability to repair itself and the lesions develop into degenerative arthritis. Overcoming the low regenerative capacity of the cartilage cells and the Hayflick limit poses a challenge for the therapy of osteochondral defects. Composite scaffolds with appropriate biomechanical properties combined with a suitable blend of proliferation and differentiation factors could be a solution. The aim of this in vitro study was to develop a novel functionalised hydrogel with an integrated drug delivery system stimulating articular cartilage regeneration. MATERIAL AND METHODS: Injectable collagen/ hyaluronic acid/fibrin composite hydrogel was mixed with nanofibre-based microparticles. These were loaded with ascorbic acid and dexamethasone. In addition, the effect of thrombocyte-rich solution (TRS) was studied. The gels seeded with mesenchymal stem cells (MSCs) were cultivated for 14 days. The viability, proliferation and morphology of the cells were evaluated using molecular and microscopic methods. Scaffold degradation was also assessed. RESULTS: The cultivation study showed that MSCs remained viable in all experimental groups, which indicated good biocompatibility of the gel. However, the number of cells in the groups enriched with microparticles was lower than in the other groups. On the other hand, confocal microscopy showed higher cell viability and rounded morphology of the cells, which can be associated with chodrogenic differentiation. The scaffolds containing microparticles showed significantly higher stability during the 14-day experiment. DISCUSSION: Our results suggest that the addition of microparticles to the scaffold improved cell differentiation into the chondrogenic lineage, resulting in a lower proliferation rate. Cell viability was better in the groups enriched with microparticles that served as an efficient drug delivery system. In addition, the presence of microparticles slowed down gel degradation which can help achieve sufficient stability of the system for the time frame required for cartilage regeneration. CONCLUSIONS: The novel approach described here produced an efficient system where microparticles served as a drug delivery system and stabilised the gel for prolonged periods of time. These characteristics play an important role in the development of scaffolds for cartilage regeneration. In the future the results of these in vitro experiments will be verified in an in vivo study.
Keywords: trombocyty; Osteonecrosis; kultivované buňky; Tissue Engineering; Osteochondritis Dissecans; Antioxidants; Hydrogel, Polyethylene Glycol Dimethacrylate; antiflogistika; injekce; Mesenchymal Stem Cells; lékové transportní systémy; Regeneration; regenerace; osteonekróza; antioxidancia; kloubní chrupavka; Cells, Cultured; mezenchymální kmenové buňky; osteochondritis dissecans; Anti-Inflammatory Agents; Humans; kyselina askorbová; dexamethason; Injections; tkáňové inženýrství; Cartilage, Articular; Dexamethasone; Drug Delivery Systems; PEG-DMA hydrogel; Blood Platelets; testování materiálů; Materials Testing; Ascorbic Acid; lidé